Gastropods are faced with potential environmental hazards in Kuala Langsa, Aceh - Dwi Putri Oktavia Sinabariba; Cut Salsabila Meutia Sari; Meli Supiani; Gita Prilien Aibekob; Batubara, Yusraini; Purba, Putri Ayu Anjelica (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Kuala Langsa Peninsula is a geographical region that is often developed as a site of habitat. The surrounding nature of Kuala Langsa is an environment of biodiversity that contains gastropods. There are also several mangrove areas throughout Kuala Langsa with certain characteristics, under certain conditions and status, which are ecological or non-ecological conservation. The purpose of this investigation is to determine the level of pollution that occurs in the port of Kuala Langsa by looking at the value of the index of gastropodic diversity. The research uses the quantitative method with the Shannon-Wienner diversity index formula and sampling using the square tranche technique. The results show that diversity from common and detected low quality is based on the total number of species in a community found, as well as very similar types of organisms, resulting in low diversity coefficient values and water quality belonging to moderate pollution. The conclusion is that the total number of gastropods is 1,064 individuals from 9 families and 19 species on the three research locations. It can be concluded that the highest value of the diversity index obtained with the data is at station II, which is 2, whereas the lowest diversity Index value at station III is at 1.86 and is followed by station I at 1.91, as long as from the data the variability index value belongs to the type of moderate polluted waters.